Pullback Attractor of a Non-Autonomous Model for Epitaxial Growth (Communications in Mathematical Research, 2019)
In this paper, we consider a non-autonomous model for epitaxial growth.It is shown that a pullback attractor of the model exists when the external force hasexponential growth.
Keywords: pullback attractor; non-autonomous model; asymptotic compactness